The Use of Risk Scores for Thromboprophylaxis in Medically Ill Patients—Rationale and Design of the RICO trial - Dentali, Francesco; Campanini, Mauro; Bonaventura, Aldo; Fontanella, Luca; Zuretti, Francesca; Tavecchia, Luca; Mumoli, Nicola; Gnerre, Paola; Ventrella, Francesco; Giustozzi, Michela; Valerio, Antonella; Fontanella, Andrea (TH Open, 2024)
Background Venous thromboembolism (VTE) in hospitalized medically ill patients is a significant cause of morbidity and mortality. Guidelines suggest that VTE and bleeding risk assessment models (RAMs) should be integrated into the clinical decision-making process on thromboprophylaxis. However, poor evidence is available comparing the use of a RAM versus clinical judgement in evaluating VTE and bleeding occurrence.Methods Reducing Important Clinical Outcomes in hospitalized medical ill patients (RICO) is a multicenter, cluster-randomized, controlled clinical trial (ClinicalTrials.gov Identifier: NCT04267718). Acutely ill patients hospitalized in Internal Medicine wards are randomized to the use of RAMs—namely the Padua Prediction Score and the International Medical Prevention Registry on Venous Thromboembolism Bleeding Score—or to clinical judgement. The primary study outcome is a composite of symptomatic objectively confirmed VTE and major bleeding at 90-day follow-up. Secondary endpoints include the evaluation of clinical outcomes at hospital discharge and the assessment of VTE prophylaxis prescription during the study period. In order to demonstrate a 50% reduction in the primary outcome in the experimental group and assuming an incidence of the primary outcome of 3.5% in the control group at 90-day; 2,844 patients across 32 centers will be included in the study.Discussion The RICO trial is a randomized study of clinical management assessing the role of RAMs in hospitalized medical ill patients with the aim of reducing VTE and bleeding occurrence. The study has the potential to improve clinical practice since VTE still represents an important cause of morbidity and mortality in this setting.
Keywords: medical patients; venous thromboembolism; RAMs; major bleeding; thromboprophylaxis